Rich's Glory, or Triumphant Entry into Covent Garden - Hogarth, William (Tufts Archival Research Center, 2008)
Facsimile of a caricature by Hogarth, referring to the removal of Rich from Lincoln's Inn Fields to the New Theatre, which was opened December 7th, 1732. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.